2017
DOI: 10.1177/2050640617708953
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota, bile acids and their correlation in primary sclerosing cholangitis associated with inflammatory bowel disease

Abstract: Background: Patients with primary sclerosing cholangitis associated with inflammatory bowel disease (PSC-IBD) have a very high risk of developing colorectal neoplasia. Alterations in the gut microbiota and/or gut bile acids could account for the increase in this risk. However, no studies have yet investigated the net result of cholestasis and a potentially altered bile acid pool interacting with a dysbiotic gut flora in the inflamed colon of PSC-IBD. Aim: The aim of this study was to compare the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
73
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 54 publications
12
73
0
3
Order By: Relevance
“…As described in former sections, increased abundance of Veillonellaceae and Veillonella have been associated with higher systemic inflammation, endotoxemia and HE in patients with liver cirrhotics [188,214,216,246]. It is noteworthy in this study that the amount of Veillonella showed strong correlations to multiple bile acid profiles in the feces (e.g., total primary and secondary BAs levels, primary BAs/secondary BAs ratio, and sulfo-conjugates) [246]. Veillonella is also known as a 7α-dehydroxylating bacteria, promoting secondary BA formation in the intestine [253].…”
Section: Primary Sclerosing Cholangitis (Psc)mentioning
confidence: 72%
See 4 more Smart Citations
“…As described in former sections, increased abundance of Veillonellaceae and Veillonella have been associated with higher systemic inflammation, endotoxemia and HE in patients with liver cirrhotics [188,214,216,246]. It is noteworthy in this study that the amount of Veillonella showed strong correlations to multiple bile acid profiles in the feces (e.g., total primary and secondary BAs levels, primary BAs/secondary BAs ratio, and sulfo-conjugates) [246]. Veillonella is also known as a 7α-dehydroxylating bacteria, promoting secondary BA formation in the intestine [253].…”
Section: Primary Sclerosing Cholangitis (Psc)mentioning
confidence: 72%
“…Their study indicated that Enterococcus and Lactobacillus were increased in PSC patients without liver cirrhosis, LT or concomitant IBD [241], although the dysbiosis had been associated with liver cirrhosis [38,98] and IBD [195]. The increase in Fusobacterium, also reported later by Torres et al [246], might be meaningful, when considering its known linking with colorectal cancer in PSC patients [247]. nishiishi et al [248] demonstrated significant increases in Escherichia, Lachnospiraceae and Megasphera in the patients with PSC-IBD compared with controls.…”
Section: Primary Sclerosing Cholangitis (Psc)mentioning
confidence: 72%
See 3 more Smart Citations